The impact of German macroeconomic data announcements on the Czech financial market - Michala Moravcová (Charles University in Prague, Institute of Economic Studies (IES), 2015)
This paper analyzes the impact of German macroeconomic news announcements on the Czech financial market - as proxied by EUR/CZK exchange rate returns - over three sub-periods: the financial crisis period (2008-2009), the post-crisis period (2010-11/2013) and the currency intervention period (11/2013-2014). Both symmetric and asymmetric models from the class of generalized autoregressive conditional heteroscedasticity (GARCH) models are applied. Macroeconomic shocks (GDP, ZEW, IFO, factory orders, industrial production, Purchasing manager's indexes (PMI) from service and production sectors) are constructed as deviations form expected values. The results suggest that announcement of German GDP and IFO index calm the exchange rate volatility during the 7-year total examined time period. Splitting the time series into 3 individual sub-periods the results suggest that announcements of GDP, factory orders decrease and announcements of industrial production, IFO index increase the conditional volatility during financial crises. Furthermore, announcements of GDP and ZEW index calm the exchange rate's conditional volatility during the post-crises period. Finally, announcements of GDP data and PMI index form production sector increase conditional variance during the central bank's currency interventions. Moreover, announcement of higher IFO index depreciates the CZK value during the post-crisis period.
Keywords: 330; exchange rate volatility; heteroscedasticity; GARCH; EGARCH; macroeconomic news